Hygrothermal aging resistant copolyester, preparation method and application

Through the formulation and process of modified polyester materials, we can prepare copolyesters that resist moisture and heat aging, which solves the problem of rapid aging speed of polyester materials in high humidity and heat environments, and achieves the improvement of high strength and anti-aging performance. It is suitable for BOPET composite films.

CN120248296APending Publication Date: 2025-07-04ANHUI GUOFENG NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510345422.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The existing polyester materials age quickly in high humidity and heat environments, which affects their outdoor application range. The existing modification methods have limited effects.

Method used

The slurry is prepared by adding raw materials such as 2,3-epoxypropyl acrylate, 1,5-pentanediol, 1,4-butylene glycol and other raw materials, and the dry modified ethylene glycol antimony, tetrabutyl titanate and triethyl phosphite for modification. Combined with high vacuum esterification and final polycondensation reaction, anti-humidity and heat aging copolyester are prepared, and then the BOPET composite film is prepared.

Benefits of technology

The prepared PET polyester slices show excellent anti-aging ability and high-strength machine tensile properties in high humidity and heat environments, and are suitable for the preparation of BOPET composite films that are anti-humid heat aging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248296A_ABST
    Figure CN120248296A_ABST
Patent Text Reader

Abstract

The invention discloses damp-heat aging resistant copolyester, a preparation method and application, and belongs to the field of macromolecular polyester materials. The damp-heat aging resistant copolyester comprises the following raw materials in parts by mass: 100 parts of terephthalic acid; 26 to 30 parts of 2, 3-epoxy propyl acrylate; 2 to 4 parts of 1, 5-pentanediol; 2 to 4 parts of 1, 4-butanediol; 50 to 60 parts of ethylene glycol; 0.6-1 part of nano clay modified by organic quaternary ammonium salt; 0.04 to 0.1 part of tetrabutyl titanate; 0.04 to 0.1 part of dried and modified ethylene glycol antimony; and 0.02 to 0.1 part of triethyl phosphite. By adding three types of modified components for copolymerization modification, the prepared PET polyester chip has the advantages of excellent damp-heat aging resistance and high-strength machine tensile property, and can be used for preparing the damp-heat aging resistant BOPET composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of polymer polyester materials, and particularly relates to a moisture and heat aging resistant copolyester, a preparation method and an application thereof. Background Art

[0002] Polyester chips generally refer to polyester raw materials obtained by polymerization production, and the product specifications are generally sheet-like particles about 4*5*2 mm. Its mainstream process route is the direct esterification method (PTA method), which has the advantages of low raw material consumption and short reaction time. Since the 1980s, it has become the main process and the preferred technical route for polyester. Generally, due to the advantages of high strength, large modulus, good impact and fatigue resistance of polyester materials, they are widely used in the field of packaging film materials.

[0003] However, in the outdoor environment, the use of polyester materials is affected by adverse factors such as temperature, humidity and mechanical action, and the molecular chain segments are continuously hydrolyzed, resulting in a gradual decline in various aspects of their performance. Especially under high humidity and heat environment conditions, the aging speed increases significantly, seriously affecting its use in the outdoor environment and restricting its outdoor application range.

[0004] Therefore, the related modification of PET polyester chips to make them have the ability to resist moisture and heat aging has become one of the research focuses of packaging film enterprises. At present, there are certain deficiencies in the related modification patents. For example, in the method disclosed in Chinese invention patent CN202311597719, a moisture and heat aging resistant functional additive is used, but its effect is limited; in the method disclosed in Chinese invention patent CN 201810287115, the end is capped with a polyfunctional epoxy compound, and the machine performance still needs to be further improved. Summary of the Invention

[0005] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a moisture and heat aging resistant copolyester, a preparation method and an application thereof, and solve the problems in the prior art.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A moisture and heat aging resistant copolyester, comprising the following raw materials in parts by mass:

[0008]

[0009] Further, the preparation process of the dried and modified antimony glycolate is as follows: placing the antimony glycolate and activated carbon in an evaporating dish, and baking at a temperature of 80-90°C for 12-15 h to obtain it.

[0010] The above-mentioned preparation method of a moisture and heat aging resistant copolyester comprises the following steps:

[0011] S1. Prepare Slurry 1 by mixing terephthalic acid, ethylene glycol, 2,3-epoxypropyl acrylate, 1,5-pentanediol, and 1,4-butanediol. Then add organo-quaternary ammonium salt modified nano-clay and tetrabutyl titanate. After that, add dried and modified antimony glycolate and triethyl phosphite to modify Slurry 1 to obtain Slurry 2. Continuously inject Slurry 2 into the esterification system for esterification reaction to obtain the initial esterification product.

[0012] S2. Increase the vacuum degree of the esterification system to make it in the high vacuum stage. Under the condition of high vacuum, the polyester prepolymer undergoes a final polycondensation reaction to obtain a polyester melt.

[0013] S3. Cool, solidify, and pelletize the polyester melt to obtain PET polyester chips. After aging, perform recrystallization to obtain the anti-hydrothermal aging copolyester.

[0014] Further, the conditions of the esterification reaction are: heating to 240 - 260 °C at a heating rate of 10 - 12 °C / min, the pressure during the reaction is 0.22 - 0.25 MPa, and the reaction time is 30 - 35 min.

[0015] Further, the pressure in the high vacuum stage is -0.1 MPa.

[0016] Further, the dried and modified antimony glycolate is added to the reaction kettle together with tetrabutyl titanate and triethyl phosphite, and the addition order is fixed as triethyl phosphite, antimony glycolate, and tetrabutyl titanate.

[0017] The application of the above anti-hydrothermal aging copolyester in the preparation of BOPET composite films.

[0018] Further, the steps for preparing the BOPET composite film include:

[0019] Step 1. Melt and co-extrude the anti-hydrothermal aging copolyester and ordinary anti-sticking PET masterbatch through a twin-screw extruder, extrude from the die head, and slowly cast to form a uniform melt. Among them, the core layer of the main extruder is the anti-hydrothermal aging copolyester, and the upper and lower surface layers are ordinary anti-sticking PET masterbatch (Yizheng Chemical Fiber FG610).

[0020] Step 2. Send the uniform melt into a casting machine for casting.

[0021] Step 3. Stretch the cast sheet longitudinally and transversely in sequence through a stretching machine, and perform online coating synchronously during biaxial stretching. The coating solution used is a coating solution containing fluorosilicon nanomaterials to obtain the BOPET composite film.

[0022] Further, the temperatures of each part of the twin-screw extruder are set as follows: the feeding section is 208 - 253 °C, the compression section is 253 - 264 °C, and the homogenization section is 264 - 279 °C.

[0023] Further, in the casting machine, the temperature of the first cold drum casting is 26 - 32 °C, the temperature of the second cold drum casting is 32 - 46 °C, and the voltage of the electrostatic film-attaching wire is 9.5 KV.

[0024] Advantages of the present invention:

[0025] 1. The present invention modifies the slurry with 2,3-epoxypropyl acrylate, 1,5-pentanediol, and 1,4-butanediol to prepare the primary slurry in one step and performs secondary modification on the basis of the primary slurry, with simple operation and little environmental pollution.

[0026] 2. When preparing PET polyester chips, the method of copolymer modification with three types of modifying components is innovatively added, so that the prepared PET polyester chips have the advantages of excellent resistance to hygrothermal aging and high-strength machine stretching performance, and can be used to prepare BOPET composite films with resistance to hygrothermal aging. Description of the drawings

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, for those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0028] Figure 1 is the polymerization reaction flow chart of the present invention;

[0029] Figure 2 is the structural formula of 2,3-epoxypropyl acrylate;

[0030] Figure 3 is the physical diagram of the sample in Example 1 of the present invention;

[0031] Figure 4 is the physical diagram of the sample in Example 2 of the present invention;

[0032] Figure 5 is the physical diagram of the sample in Example 3 of the present invention;

[0033] Figure 6 is the physical diagram of the sample in Comparative Example 1 of the present invention. Detailed implementation manners

[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0035] As Figure 1 shown, a moisture and heat aging resistant copolyester comprises the following raw materials in parts by mass:

[0036]

[0037]

[0038] Among them, the structural formula of 2,3-epoxypropyl acrylate is as Figure 2 shown;

[0039] The preparation process of the dried and modified antimony glycolate is as follows: Place the antimony glycolate and activated carbon in an evaporating dish and bake at a temperature of 80 - 90 °C for 12 - 15 h to obtain the dried and modified antimony glycolate.

[0040] The dried and modified antimony glycolate needs to be added to the reaction kettle together with tetrabutyl titanate and triethyl phosphite, and the addition order needs to be in the fixed order of triethyl phosphite, antimony glycolate, and tetrabutyl titanate.

[0041] The organoquaternary ammonium salt modified nanoclay needs to be mixed evenly with ethylene glycol before use and added in the esterification stage.

[0042] A preparation method of a moisture and heat aging resistant copolyester comprises:

[0043] S1, Prepare a slurry one from terephthalic acid, ethylene glycol, 2,3-epoxypropyl acrylate, 1,5-pentanediol, and 1,4-butanediol, then add the organoquaternary ammonium salt modified nanoclay and tetrabutyl titanate, and then add the dried and modified antimony glycolate and triethyl phosphite to modify the slurry one to obtain a slurry two; Continuously inject the slurry two into an esterification system for esterification reaction to obtain an initial esterification product;

[0044] S2, First, maintain the vacuum parameter of the polymerization device at a low vacuum stage for no less than 30 minutes to facilitate the pre-polycondensation reaction of the initial esterification product, and then increase the vacuum degree of the polymerization device to make the polymerization device in a high vacuum stage. Under the condition of high vacuum, the polyester pre-polycondensation product undergoes a final polycondensation reaction to obtain a polyester melt;

[0045] S3, The polyester melt is cooled, solidified, and pelletized to obtain PET polyester chips. After aging for 1 h, low-temperature recrystallization is carried out to obtain the moisture and heat aging resistant copolyester;

[0046] Among them, in S1, the conditions for the esterification reaction are as follows: heating up to 240 - 260°C at a heating rate of 10 - 12°C / min, the pressure during the reaction is 0.22 - 0.25 MPa, and the reaction time is 30 - 35 min.

[0047] In S2, the pressure in the low vacuum stage is -0.05 MPa, and the pressure in the high vacuum stage is -0.1 MPa.

[0048] The intrinsic viscosity of the moisture and heat aging resistant polyester prepared in S3 is 0.6 - 0.8 dL / g.

[0049] The above moisture and heat aging resistant copolyester can also be used to prepare a BOPET composite film, and the preparation method includes the following steps:

[0050] Step 1, melt and perform three - layer co - extrusion of the moisture and heat aging resistant copolyester and the ordinary anti - sticking PET masterbatch through a twin - screw extruder, extrude from the die head, and slowly cast to form a uniform melt; among them, the core layer of the main extruder is the moisture and heat aging resistant copolyester, and the upper and lower surface layers are ordinary anti - sticking PET masterbatch; the temperatures of each part of the twin - screw extruder are set as follows: feeding section (208 - 253°C), compression section (253 - 264°C), homogenization section (264 - 279°C);

[0051] Step 2, send the uniform melt into a casting machine for casting. Among them, the temperatures of each part of the casting machine are set as follows: the first cold drum for casting (26 - 32°C), the second cold drum for casting (32 - 46°C), and the electrostatic film - attaching wire voltage (9.5 KV);

[0052] Step 3, longitudinally and transversely stretch the cast sheet through a stretching machine in sequence, and perform on - line coating synchronously during biaxial stretching. The coating solution used is a coating solution containing fluorosilicon nanomaterials to obtain a BOPET composite film; the raw material used for on - line coating is a coating solution containing fluorosilicon nanomaterials, and the fluorosilicon nanomaterials account for 5% of the total mass of the coating solution;

[0053] Among them, the temperatures of each part for longitudinal stretching are set as follows: the pre - heating zone of the longitudinal stretching roller (62 - 72°C), the stretching zone (72 - 82°C), the cooling zone (25 - 40°C), and the stretching ratio is 3.5 - 5.5; the temperatures of each part for transverse stretching are set as follows: the pre - heating zone temperature of the transverse stretching roller (98 - 100°C), the stretching zone (110 - 125°C), the cooling zone (57 - 62°C), the shaping zone (225 - 240°C), and the stretching ratio is 3.5 - 5.5. After longitudinal and transverse stretching, a moisture and heat aging resistant BOPET composite film is made.

[0054] The following examples and comparative examples are used to illustrate the preparation process of the moisture and heat aging resistant copolyester; among them, the sources of raw materials used in the examples and comparative examples are as follows:

[0055] Terephthalic acid Hengli Petrochemical (Dalian) Co., Ltd.;

[0056] 2,3-Epoxypropyl acrylate Anhui Youya Chemical Co., Ltd.;

[0057] 1,5-Pentanediol Shanghai Macklin Biochemical Co., Ltd.;

[0058] 1,4-Butanediol Shanghai Macklin Biochemical Co., Ltd.;

[0059] Ethylene glycol Jiangsu Yongfeng Chemical Reagent Co., Ltd.;

[0060] The organo-quaternary ammonium salt modified nano-clay was self-made. The preparation process was as follows: Using cetyltrimethylammonium chloride as the modifier, mixing it with hydrochloric acid to produce hydrochloride and dissociating into amine cations, and then mixing it with clay to exchange the hydrated cations between the clay layers; The obtained product was the organo-quaternary ammonium salt modified nano-clay; Among them, cetyltrimethylammonium chloride was from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0061] Tetrabutyl titanate Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0062] The dried and modified antimony glycolate was self-made;

[0063] Triethyl phosphite Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0064] Cetyltrimethylammonium chloride was from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0065] Example 1

[0066] A preparation method of a moisture and heat aging resistant copolyester, comprising the following steps:

[0067] Using 6.1 kg of terephthalic acid, 1.8 kg of 2,3-epoxypropyl acrylate, 0.18 kg of 1,5-pentanediol, 0.122 kg of 1,4-butanediol, 3.0 L of ethylene glycol, 2.75 g of the dried and modified antimony glycolate as the catalyst, 1.4 mL of triethyl phosphite as the stabilizer, 3 mL of tetrabutyl titanate, and 0.04 kg of the organo-quaternary ammonium salt modified nano-clay.

[0068] Feeding into the reaction kettle, carrying out pulping for 20 min to ensure no particle precipitation.

[0069] Maintaining a uniform and stable heating rate of 5 °C / min, heating to 245 °C, and starting the esterification step.

[0070] After the esterification water reaches the theoretical value (1300 mL), keep the equipment at atmospheric pressure and the temperature at 245 °C.

[0071] Use multiple vacuum pumps to evacuate the air and keep the equipment pressure at -0.1 MPa.

[0072] Set the reaction temperature of the equipment at 270 °C and maintain it for 20 min.

[0073] After the reaction is completed, pressurize the reaction kettle to 0.25 MPa, connect the cooling water tank and the granulator to carry out granulation to obtain sliced particles. After aging for one hour, carry out low-temperature recrystallization; the obtained sample is as Figure 3 shown.

[0074] Subsequently, carry out casting, longitudinal stretching, transverse stretching and winding of the particles.

[0075] Example 2

[0076] With the dosage of terephthalic acid being 6.2 kg, the dosage of 2,3-epoxypropyl acrylate being 1.7 kg, the dosage of 1,5-pentanediol being 0.16 kg, the dosage of 1,4-butanediol being 0.132 kg, the dosage of ethylene glycol being 3.1 L, the catalyst being 2.7 g of dried and modified antimony glycolate, the stabilizer being 1.3 mL of triethyl phosphite, 3.2 mL of tetrabutyl titanate, and 0.043 kg of organo-quaternary ammonium salt modified nanoclay.

[0077] Charge the materials into the reaction kettle and carry out pulping for 20 min to ensure no particle precipitation.

[0078] Keep a uniform and stable heating rate of 5 °C / min and heat up to 245 °C to start the esterification step.

[0079] After the esterification water reaches the theoretical value (1300 mL), keep the equipment at atmospheric pressure and the temperature at 245 °C.

[0080] Use multiple vacuum pumps to evacuate the air and keep the equipment pressure at -0.1 MPa.

[0081] Set the reaction temperature of the equipment at 270 °C and maintain it for 20 min.

[0082] After the reaction is completed, pressurize the reaction kettle to 0.25 MPa, connect the cooling water tank and the granulator to carry out granulation to obtain sliced particles. After aging for one hour, carry out low-temperature recrystallization; the obtained sample is as Figure 4 shown.

[0083] Subsequently, carry out casting, longitudinal stretching, transverse stretching and winding of the particles.

[0084] Example 3

[0085] With the dosage of terephthalic acid being 6.14 kg, the dosage of 2,3-epoxypropyl acrylate being 1.72 kg, the dosage of 1,5-pentanediol being 0.168 kg, the dosage of 1,4-butanediol being 0.13 kg, the dosage of ethylene glycol being 3.1 L, the catalyst being 2.8 g of dried and modified antimony glycolate, the stabilizer being 1.38 mL of triethyl phosphite, 3.2 mL of tetrabutyl titanate, and 0.045 kg of organo-quaternary ammonium salt modified nano-clay.

[0086] Charge the materials into the reaction kettle and carry out pulping for 20 min to ensure no particle precipitation.

[0087] Maintain a uniform and stable heating rate of 5 °C / min and heat up to 245 °C to start the esterification step.

[0088] After the esterification water reaches the theoretical value (1300 mL), keep the equipment at normal pressure and the temperature at 245 °C.

[0089] Use multiple vacuum pumps to evacuate and keep the equipment pressure at about -0.1 MPa.

[0090] Set the equipment reaction temperature at 270 °C and maintain for 20 min.

[0091] After the reaction is completed, pressurize the reaction kettle to 0.25 MPa, connect the cooling water tank and the pelletizer to carry out pelletizing to obtain sliced particles. After aging for one hour, carry out low-temperature recrystallization; the obtained sample is as Figure 5 shown.

[0092] Subsequently, carry out casting, longitudinal stretching, transverse stretching and winding of the particles.

[0093] Comparative Example 1

[0094] With the dosage of terephthalic acid being 6.4 kg, the dosage of ethylene glycol being 3.1 L, the catalyst being 2.6 g of dried and modified antimony glycolate, and the stabilizer being 1.4 mL of trimethyl phosphate.

[0095] Charge the materials into the reaction kettle and carry out pulping for 20 min to ensure no particle precipitation.

[0096] Maintain a uniform and stable heating rate of 5 °C / min and heat up to 248 °C to start the esterification step.

[0097] After the esterification water reaches the theoretical value (1300 mL), keep the equipment at normal pressure and the temperature at 245 °C.

[0098] Use multiple vacuum pumps to evacuate and keep the equipment pressure at about -0.1 MPa.

[0099] Set the equipment reaction temperature at 265 °C and maintain for 20 min.

[0100] After the reaction is completed, pressurize the reaction kettle to 0.25 MPa, connect the cooling water tank and the granulator, and granulate to obtain slice particles; the obtained physical sample is as Figure 6 shown.

[0101] Subsequently, the particles are cast into films, longitudinally stretched, laterally stretched, and wound up.

[0102] Performance Testing

[0103] Perform performance testing on the wound films obtained in Examples 1-3 and the comparative example. The results are shown in Table 1:

[0104] Table 1 Performance Testing Results of Polyester Films Prepared in Examples 1-3 and Comparative Example 1

[0105]

[0106] Note: Resistance to damp heat aging means aging at 80 °C and 85% humidity for 36 hours.

[0107] It can be seen from Table 1 that:

[0108] For the anti-damp heat aging copolyesters obtained by the method of this application in Examples 1-3, compared with the conventional PET slice in Comparative Example 1, under the same aging environment (aging at 80 °C and 85% humidity for 36 hours), performance indexes such as viscosity, terminal carboxyl group content, tensile strength, and elongation at break of Examples 1-3 basically do not change before and after the anti-damp heat aging test, and the anti-damp heat aging effect is good. On the contrary, all performance data of the conventional PET slice in Comparative Example 1 change significantly before and after the anti-damp heat aging test, indicating that the anti-damp heat aging effect of the conventional PET slice in Comparative Example 1 is not good. In summary, the anti-damp heat aging copolyester prepared by this patent has good anti-damp heat aging ability.

[0109] In the description of this specification, the descriptions referring to terms such as "one embodiment", "example", "specific example", etc. mean that the specific features, structures, materials, or characteristics described in connection with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in a suitable manner in any one or more embodiments or examples.

[0110] The above shows and describes the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. What is described in the above embodiments and the specification only illustrates the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention will have various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed.

Claims

1. A copolyester resistant to damp heat aging, characterized in that, It includes the following raw materials in parts by mass:

2. The anti-moisture and heat aging copolyester according to claim 1, characterized in that, The preparation process of the dried and modified antimony glycolate is as follows: Place the antimony glycolate and activated carbon in an evaporating dish and bake at a temperature of 80 - 90 °C for 12 - 15 h to obtain it.

3. The preparation method of a copolyester resistant to damp heat aging according to claim 1 or 2, characterized in that, It includes the following steps: S1, Prepare slurry one with terephthalic acid, ethylene glycol, 2,3-epoxypropyl acrylate, 1,5-pentanediol, and 1,4-butanediol. Then add organo-quaternary ammonium salt-modified nanoclay and tetrabutyl titanate. After that, add the dried and modified antimony glycolate and triethyl phosphite to modify slurry one to obtain slurry two; Continuously inject slurry two into the esterification system for esterification reaction to obtain an initial esterification product; S2, Increase the vacuum degree of the esterification system to make the esterification system in a high vacuum stage. Under the condition of high vacuum, the polyester prepolymer undergoes a final polycondensation reaction to obtain a polyester melt; S3, The polyester melt is cooled, solidified, and pelletized to obtain PET polyester chips. After aging, recrystallization is carried out to obtain a moisture and heat aging-resistant copolyester.

4. The preparation method of a moisture and heat aging resistant copolyester according to claim 3, characterized in that, The conditions of the esterification reaction are: Raise the temperature at a heating rate of 10 - 12 °C / min to 240 - 260 °C, the pressure during the reaction is 0.22 - 0.25 MPa, and the reaction time is 30 - 35 min.

5. The preparation method of a moisture and heat aging resistant copolyester according to claim 3, characterized in that, The pressure in the high vacuum stage is -0.1 MPa.

6. The preparation method of a moisture and heat aging resistant copolyester according to claim 3, characterized in that, The dried and modified antimony glycolate is added to the reaction kettle together with tetrabutyl titanate and triethyl phosphite, and the addition sequence is fixed in the order of triethyl phosphite, antimony glycolate, and tetrabutyl titanate.

7. Use of a moisture and heat aging-resistant copolyester according to claim 1 or 2 in the preparation of a BOPET composite film.

8. The application according to claim 7, wherein The steps for preparing the BOPET composite film include: Step 1, Melt and co-extrude the moisture and heat aging-resistant copolyester and ordinary anti-sticking PET masterbatch through a twin-screw extruder, extrude from the die head, and slowly cast to form a uniform melt; Among them, the core layer of the main extruder is the moisture and heat aging-resistant copolyester, and the upper and lower surface layers are ordinary anti-sticking PET masterbatch; Step 2, Feed the uniform melt into a casting machine for casting; Step 3, Stretch the cast sheet longitudinally and transversely in sequence through a stretching machine, and synchronously carry out on-line coating during biaxial stretching. The coating solution used is a coating solution containing fluorosilicon nanomaterials to obtain a BOPET composite film.

9. The application according to claim 7, characterized in that, The temperatures set for each part of the twin-screw extruder are: the feeding section is 208 - 253 °C, the compression section is 253 - 264 °C, and the homogenization section is 264 - 279 °C.

10. The application according to claim 7, wherein The temperature of the first cold drum for casting in the casting machine is 26 - 32 °C, the temperature of the second cold drum for casting is 32 - 46 °C, and the electrostatic film-attaching wire voltage is 9.5 KV.

Citation Information

Patent Citations

  • A multifunctional epoxy compound-terminated, moisture-resistant polyester film and its synthesis method

    CN108676152B

  • A kind of polyester material resistant to moisture and heat aging and preparation method thereof

    CN117659643B